Theory of Islamic Legal Philosophy Reasoning; Bayani Theory - Hudaya Nur, Dwi Utami; Dahliah, Dahliah; Fatmawati, Fatmawati; Musyahid, Ahmad (Program Studi Hukum Keluarga Islam, Universitas Islam Nusantara Al-Azhaar Lubuklinggau, 2025)
This study aims to examine the concept of bayani theory and its application in Islamic legal philosophy. This study uses a qualitative approach with a library research method. Data collection techniques were conducted through reading, collecting, and analyzing literature from books and journals. The results of the study indicate that Islamic legal philosophy demonstrates that this theory is a central pillar in classical Islamic legal epistemology. The philosophical roots of bayani theory lie in prioritizing revealed texts (nash) as the absolute source of truth and law. Bayani reasoning is based on the belief that all of God's commands and prohibitions contain meanings that can be understood through Arabic linguistic tools. Therefore, this method positions language as a central medium for understanding Sharia law. Bayani theory should be maintained as the core of Islamic legal epistemology, but it must be revitalized through reinterpretation and integration with modern social sciences to provide answers to complex legal problems in the global era.